Adsorption of anionic dye by anionic surfactant modified chitosan beads: Influence of hydrophobic tail and ionic head-group. Issue 1 (2nd January 2018) - Lin, Cuiying; Wang, Shuo; Sun, Haoqi; Jiang, Rong
ABSTRACT: In this paper, how chitosan hydrogel beads were modified by anionic surfactants (SDS, SDOS, SDBS, AOT, and DTM-12) and then used for the adsorption and removal of an anionic dye (congo red) from aqueous solutions were described. The effect of surfactant concentration, surfactant ionic head-group, and surfactant hydrophobic tail were investigated in detail. The result revealed the modified CS beads all had the obviously higher adsorption capacity than CS beads. Compared to the ionic head-group, the hydrophobic tail of the surfactant plays more important role in the adsorption, and a high adsorption capacity was observed for CS/AOT beads and CS/DTM-12 beads (both with two hydrophobic tails). The Sips isotherm model showed a good fit with the equilibrium experimental data, and the values of the heterogeneity factor ( n ) indicated heterogeneous adsorption. The adsorption kinetics analysis indicated that the pseudo-second-order rate model could better describe the adsorption process than the pseudo-first-order rate model. GRAPHICAL ABSTRACT: HIGHLIGHTS: The surfactant with double hydrophobic tails (i.e., AOT or DTM-12) impregnated CS beads was the best one among the investigated adsorbents, indicating the hydrophobic tail of the surfactant play an important role in controlling the adsorption capacity of the modified CS beads.